Long-term clinical outcomes of cochlear implantation in children with symptomatic epilepsy. (March 2016) - Di Lella, Filippo; Bacciu, Andrea; Falcioni, Maurizio; Guida, Maurizio; Vincenti, Vincenzo
Abstract: Objectives: To describe long-term clinical outcomes of cochlear implantation in deaf children with symptomatic epilepsy. Materials and methods: A retrospective data analysis review of patients implanted at the Cochlear Implant Center of the University of Parma, Italy, was performed, searching for implanted children with a confirmed diagnosis of symptomatic epilepsy. Clinical data, imaging findings, pre- and post-operative epilepsy pattern and EEG traces were analyzed; communicative skills were assessed using the Profile of Actual Linguistic Skills. Results: Search retrieved two patients affected by profound bilateral sensorineural hearing loss and symptomatic epilepsy (associated respectively with methylmalonic acidemia and cerebral palsy). After careful parental counselling both patients were offered and underwent cochlear implantation. Activation and use of cochlear implant did not determine substantial changes of pre-existing seizure pattern and EEG traces. Both patients showed substantial development of their communicative abilities. Conclusions: Cochlear implantation in children with symptomatic epilepsy did not determine variations in seizure pattern or EEG traces. Both patients experienced substantial benefit from cochlear implantation.